2017
DOI: 10.1002/jib.424
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plackett-Burman experimental design for investigating the effect of wort amino acids on flavour-active compounds production during lager yeast fermentation

Abstract: Aroma‐active higher alcohols and esters are produced intracellularly in the cytosol by fermenting lager yeast cells, which are of major industrial interest because they determine aroma and taste characteristics of the fermented beer. Wort amino acid composition and their utilization by yeast during brewer's wort fermentation influence both the yeast fermentation performance and the flavour profile of the finished product. To better understand the relationship between the yeast cell and wort amino acid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Thus, the assumption that only glutamic acid can influence final concentration of isovaleric acid in beer was not confirmed. This result may be discussed in conjunction with the findings of the study by Yin et al ., where glutamic acid was found to have a negative effect on total amino acid absorption by yeasts. Also, it can be assumed that glutamic acid addition lowered the absorption of amino acids, including leucine, the main agent of the Ehrlich pathway.…”
Section: Resultssupporting
confidence: 85%
“…Thus, the assumption that only glutamic acid can influence final concentration of isovaleric acid in beer was not confirmed. This result may be discussed in conjunction with the findings of the study by Yin et al ., where glutamic acid was found to have a negative effect on total amino acid absorption by yeasts. Also, it can be assumed that glutamic acid addition lowered the absorption of amino acids, including leucine, the main agent of the Ehrlich pathway.…”
Section: Resultssupporting
confidence: 85%
“…Among them, proline is reportedly beneficial for providing balance and softness in the taste of wine (Hu B. R. et al, 2020 ). Moreover, isoamylol, phenylethanol, and β-phenylethanol form from the amino acids leucine, phenylalanine, and phenylalanine, respectively, and are crucial flavor precursors (Chen Y. et al, 2020 ), contributing to the sweet, fresh, and bitter taste of wine (Procopio et al, 2015 ; Yin et al, 2017 ). Meanwhile, as major nitrogen sources for the survival of microorganisms, amino acids are closely related to the growth of microorganisms and production of metabolites (Park et al, 2013 ; Yang et al, 2018 ) and can interact with carbohydrates via the Maillard reaction to produce aromatic substances (Wang W. Y. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A moderate amount of higher alcohols can make baijiu more mellow and sweet, improving the quality of baijiu. However, quality problems such as bitterness and consumer discomfort can occur when higher alcohols exceed the legal limit (60). Further, in a study with Saccharomyces cerevisiae, Yin et al indicated that leucine, valine, glutamate, phenylalanine, serine and lysine were closely related to the production of ester compounds and found that the aroma compounds could be modified by adding amino acids (60,61).…”
Section: Effects Of Nitrogenous Compounds On Microbial Growth and Met...mentioning
confidence: 99%
“…However, quality problems such as bitterness and consumer discomfort can occur when higher alcohols exceed the legal limit (60). Further, in a study with Saccharomyces cerevisiae, Yin et al indicated that leucine, valine, glutamate, phenylalanine, serine and lysine were closely related to the production of ester compounds and found that the aroma compounds could be modified by adding amino acids (60,61). Susanne et al considered the relationship between amino acid composition and higher alcohols and esters in a synthetic medium fermented by different Saccharomyces cerevisiae strains (62).…”
Section: Effects Of Nitrogenous Compounds On Microbial Growth and Met...mentioning
confidence: 99%